2008
DOI: 10.1088/0004-637x/690/2/1883
|View full text |Cite
|
Sign up to set email alerts
|

OBSCURED STAR FORMATION IN INTERMEDIATE-DENSITY ENVIRONMENTS: ASPITZERSTUDY OF THE ABELL 901/902 SUPERCLUSTER

Abstract: We explore the amount of obscured star-formation as a function of environment in the A901/902 supercluster at z = 0.165 in conjunction with a field sample drawn from the A901 and CDFS fields, imaged with HST as part of the STAGES and GEMS surveys. We combine the COMBO-17 near-UV/optical SED with Spitzer 24µm photometry to estimate both the unobscured and obscured star formation in galaxies with M * > 10 10 M ⊙ . We find that the star formation activity in massive galaxies is suppressed in dense environments, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
134
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 129 publications
16
134
1
Order By: Relevance
“…1; top right). This is consistent with the findings of STAGES that the dusty red galaxies prefer the intermediate-density environment of cluster infall regions (Gallazzi et al 2009;Wolf et al 2009), and morphologically they found ∼70% to be Sa/Sb spirals with a bright nucleus or inner bar/disk, as well as a few cases of interactions or merger remnants, suggestive of galaxy harassment, interactions or mergers for their origin.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…1; top right). This is consistent with the findings of STAGES that the dusty red galaxies prefer the intermediate-density environment of cluster infall regions (Gallazzi et al 2009;Wolf et al 2009), and morphologically they found ∼70% to be Sa/Sb spirals with a bright nucleus or inner bar/disk, as well as a few cases of interactions or merger remnants, suggestive of galaxy harassment, interactions or mergers for their origin.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…It is therefore an interesting laboratory to investigate the interplay between galaxy evolution and environment. Gallazzi et al (2009) demonstrate the general suppression of star formation at higher galaxy number densities in the STAGES system, and find that a high fraction of the remaining star formation in the cluster is either obscured or dominated by old stellar populations. Therefore dusty star-forming galaxies are predominant at intermediate densities.…”
Section: Introductionmentioning
confidence: 75%
“…Though galaxies undergoing a starburst event are commonly associated with a late-type morphology (i.e., spiral, irregular, or chaotic), a non-negligible fraction of starbursts are, surprisingly, associated with early-types (Mobasher et al 2004;Poggianti et al 2009;Abramson et al 2013). Additionally, starbursts are observed in hosts that span a wide range of stellar masses (e.g., Lehnert & Heckman 1996;Elbaz et al 2011, Hilton et al 2012Ibar et al 2013), color properties (e.g., Kartaltepe et al 2010b;Kocevski et al 2011a), and environments (e.g., Marcillac et al 2008;Gallazzi et al 2009;Hwang et al 2010a;Lemaux et al 2012;Dressler et al 2013). And though some starbursting populations show morphologies indicative of a recent merging or tidal interactions, others appear primarily as undisturbed, grand-design spirals, with little evidence of recent interactions with their surroundings (see, e.g., Ravindranath et al 2006;Kocevski et al 2011a;Tadhunter et al 2011).…”
Section: Introductionmentioning
confidence: 99%